THE ETHICS OF UTERUS TRANSPLANTATION - Catsanos, Ruby (Bioethics, 2013)
Human uterus transplantation (UTx) is currently under investigation as a treatment for uterine infertility. Without a uterus transplant, the options available to women with uterine infertility are adoption or surrogacy; only the latter has the potential for a genetically related child. UTx will offer recipients the chance of having their own pregnancy. This procedure occurs at the intersection of two ethically contentious areas: assisted reproductive technologies (ART) and organ transplantation. In relation to organ transplantation, UTx lies with composite tissue transplants such as face and limb grafts, and shares some of the ethical concerns raised by these non-life saving procedures. In relation to ART, UTx represents one more avenue by which a woman may seek to meet her reproductive goals, and as with other ART procedures, raises questions about the limits of reproductive autonomy. This paper explores the ethical issues raised by UTx with a focus on the potential gap between women's desires and aspirations about pregnancy and the likely functional outcomes of successful UTx.